Resposta dos diplópodes e quilópodes à intensidade do pastejo em sistema integrado de produção de soja e bovino de corte - Trombeta, Helena Wichineski (2019)
Crop-livestock integration is an alternative for intensifying land use and increasing sustainable food production. Millipedes and centipedes of soil perform essential ecosystem functions and are bioindicators of environmental quality. This study evaluated the response of the millipedes and centipedes of the soil to the increase of grazing intensity in a crop-livestock integration, cultivated for 13 years with soybean-pasture succession. The experiment was conducted in an area of 23 hectares, which in winter is cultivated with Avena strigosa + Lolium multiflorum for continuous grazing of cattle at heights of 10, 20, 30 and 40 cm and in summer is cultivated with Glycine max for grain production. Millipedes and centipedes were collected in pitfall traps for two years, in two samples after grazing and two after soybean harvest. Millipedes were identified at family and genus level. A total of 403 centipedes and 99 millipedes were collected, totalling four collection dates. The grazing intensification reduced the abundance of centipedes, and the abundance and richness of millipedes in the soil. In the grazing heights of 30 and 40 cm there was greater richness of millipedes, which were identified as belonging to the genera Catharosoma, Leptodesmus and the Psoudonannolenidae family. The grazing height of 30 cm allows to reconcile greater abundance and richness of millipedes and centipedes in the soil with higher animal production, which contributes to the sustainability of crop-livestock integration.